2021
DOI: 10.1111/jfpe.13929
|View full text |Cite
|
Sign up to set email alerts
|

Hempseed (Cannabis sativa L.) bulk mass modeling based on engineering properties

Abstract: Hempseed (Cannabis sativa L.) owing to its excellent nutritional and pharmaceutical potential has resurrected the industrial and scientific community to exploit their processing and utilize for new food products optimization. The design and development of storage, postharvest processing and quality analysis of seeds depend upon the correlation properties with their physical parameters. In this study, the mass of hempseed is predicted as a function of its linear dimensional property, projected area and bulk see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The obtained bulk and true density values were used to determine the porosity (ε, %) of moist grain samples. Geometric properties of the grains were determined from their linear dimensions, including the geometric mean diameter ( D g , mm), sphericity ( S p ), volume ( V , mm 3 ), and surface area ( S , mm 2 ), as described by (Ramashia et al, 2018; Saini, Panghal, et al, 2022) and expressed using Equations (1–4). The tempered grain hardness ( H g ) was measured using a hardness tester (Hicon Industries), and the results were reported as kg in terms of breaking force.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained bulk and true density values were used to determine the porosity (ε, %) of moist grain samples. Geometric properties of the grains were determined from their linear dimensions, including the geometric mean diameter ( D g , mm), sphericity ( S p ), volume ( V , mm 3 ), and surface area ( S , mm 2 ), as described by (Ramashia et al, 2018; Saini, Panghal, et al, 2022) and expressed using Equations (1–4). The tempered grain hardness ( H g ) was measured using a hardness tester (Hicon Industries), and the results were reported as kg in terms of breaking force.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, it seeks to explore the nutritional and antioxidant parameters of purple wheat flour and pearled bran, with a specific focus on the impact of debranning. By examining the engineering and milling properties at different moisture levels, important information can be acquired for ensuring the development of specialized processing instruments and techniques, tailored to colored wheat (Saini, Panghal, et al, 2022). Additionally, the nutritional evaluation will shed light on the potential applications of purple wheat in food commerce, highlighting its nutritional and antioxidant qualities.…”
mentioning
confidence: 99%
“…Taheri-Garavand et al ( 2012) [42] also reported hempseed BD and TD in a slightly different range (BD: 563.67-556.23 kg/m 3 and TD: 1034.63-902.35 kg/m 3 ) compared to those obtained in this study. Several authors indicate that the observed differences in the physical properties of different seed grades are attributed to underlying structural variations and inherent morphological differences [44]. Both density and particle size are important indexes for estimating the quality of hempseeds as a food material.…”
Section: Physicochemical Characterisation Of Dehulled Hempseedsmentioning
confidence: 99%
“…Toben et al [11] looked at the implementation of mathematical models to predict new Cannabis use by urine drug testing: it is time to move forward, while Abramson et al [12] considered the importance of mathematical models to explore the effects of marijuana and other plant based products on learning and memory in their respective study. Saini et al [13] discussed a topic entitled 'Hempseed (Cannabis sativa L) bulk mass modelling based on engineering properties in their study'. The present study is based on a mathematical model on control/eradication of consumption of Cannabis sativa.…”
Section: Introductionmentioning
confidence: 99%